Medical cannabis in the management of musculoskeletal pain: a systematic review of clinical trials - Przemysław Płatek; Laura Piejko (Physiotherapy Review)
Cannabinoids not only act through classical cannabinoid receptors but also influence a wide range of physiological processes via numerous cellular signaling pathways. In this paper, we focus on two of the most extensively studied cannabinoids: delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD). Recent scientific findings suggest that cannabinoids may be therapeutically beneficial for conditions such as neurodegenerative disorders, seizures, nausea and vomiting, insomnia, neuropathic pain, excessive muscle tension, fibromyalgia, osteoarthritis (OA), rheumatoid arthritis (RA), and chronic wounds. Aims: The aim of this study was to summarize the current state of knowledge regarding the therapeutic potential of medical cannabis in the management of musculoskeletal pain. Materials and Methods: We conducted a systematic search of scientific databases (PubMed, Medline, Google Scholar, and the PEDro Database) as well as gray literature sources for articles published between January 1, 2013, and January 1, 2024. Eligible publications were full-text English-language reports that examined various approaches to medical cannabis therapy for musculoskeletal pain, including diverse cannabinoid formulations and adminis tration methods. Outcomes of interest included pain intensity, motor function, sleep quality, and health-related quality of life. Results: The search yielded 148 articles, of which 13 met the inclusion criteria. Overall, medical cannabis was generally well tolerated and was associated with significant pain reduction, improved motor function, enhanced sleep quality, and overall improvements in health-related quality of life. Conclusions: Although early clinical evidence supports the efficacy of medical cannabis in managing musculoskeletal pain, the methodological quality of the included studies limits the strength of these conclusions. Larger and more rigorously designed randomized controlled trials are needed to further clarify the role of medical cannabis therapy in musculoskeletal pain management